Tindak Tutur Ekspresif dalam Kolom Komentar Instagram @Anggy_Umbara pada Poster Film Vina Sebelum 7 Hari - Putri, Dini Aoulia; Mulyaningsih, Indrya; Nurpadillah, Veni (Universitas Pamulang, 2025)
The purpose of this study is to describe the types of expressive and deep speech acts in the comments column of the Instagram account @Anggy_Umbara on the film poster Vina Sebelum 7 Hari, and to compile a learning assessment instrument for descriptive texts at the junior high school level as a utilization of the research results. This research method is a type of descriptive qualitative research. The data source in this study is the film poster Vina Sebelum 7 Hari which was posted by the official Instagram account of a film director, namely Anggy Umbara with the account name @Anggy_Umbara. The data for this study are excerpts from speech in the comments column of the official Instagram account @Anggy_Umbara as the director of the film Vina Sebelum 7 Hari on the film poster teaser and the first day of screening poster in theaters, with a data collection period of one period, namely March-May 2024. This study uses data collection techniques with documentation techniques, free listening, speaking, and taking notes. This study uses the analysis technique of the referential and pragmatic matching method. The results of the study found eight types of expressive speech acts in the comments column of the Instagram account @Anggy_Umbara on the upload of the film poster Vina Sebelum 7 Hari, namely: expressive speech acts of praise. Expressive speech acts of criticism, expressive speech acts of suggestions, expressive speech acts of curses, expressive speech acts of complaints, expressive speech acts of gratitude, expressive speech acts of congratulations and expressive speech acts of condolences with a total data of 99 utterances. The results of the analysis showed 38 data of expressive speech of praise, 17 data of expressive speech of criticism, six data of expressive speech of suggestions, four data of expressive speech of curses, 10 data of speech complaints, five data of gratitude, four data of congratulations, and 18 data of condolences. This research has several important implications both in the fields of language and knowledge. The types of expressive speech acts reflect the practice of using language that can be applied, about how the speech responds to something emotionally. Cognitively, this research provides an effective learning assessment instrument product, where the data sources and research data provide a real picture of how individuals understand and interact with their surroundings later.